Cellulosomics, a gene-centric approach to investigating the intraspecific diversity and adaptation of Ruminococcus flavefaciens within the rumen. - Jennifer M Brulc (Public Library of Science (PLoS), 2011)
Background The bovine rumen maintains a diverse microbial community that serves to break down indigestible plant substrates. However, those bacteria specifically adapted to degrade cellulose, the major structural component of plant biomass, represent a fraction of the rumen microbiome. Previously, we proposed scaC as a candidate for phylotyping Ruminococcus flavefaciens, one of three major cellulolytic bacterial species isolated from the rumen. In the present report we examine the dynamics and diversity of scaC-types both within and between cattle temporally, following a dietary switch from corn-silage to grass-legume hay. These results were placed in the context of the overall bacterial population dynamics measured using the 16S rRNA. Principal findings As many as 117 scaC-types were estimated, although just nineteen were detected in each of three rumens tested, and these collectively accounted for the majority of all types present. Variation in scaC populations was observed between cattle, between planktonic and fiber-associated fractions and temporally over the six-week survey, and appeared related to scaC phylogeny. However, by the sixth week no significant separation of scaC populations was seen between animals, suggesting enrichment of a constrained set of scaC-types. Comparing the amino-acid translation of each scaC-type revealed sequence variation within part of the predicted dockerin module but strong conservation in the N-terminus, where the cohesin module is located. Conclusions The R. flavefaciens species comprises a multiplicity of scaC-types in-vivo. Enrichment of particular scaC-types temporally, following a dietary switch, and between fractions along with the phylogenetic congruence suggests that functional differences exist between types. Observed differences in dockerin modules suggest at least part of the functional heterogeneity may be conferred by scaC. The polymorphic nature of scaC enables the relative distribution of R. flavefaciens strains to be examined and represents a gene-centric approach to investigating the intraspecific adaptation of an important specialist population.